Modeling of the influence of light quality on the growth of microalgae in a laboratory scale photo-bio-reactor irradiated by arrangements of blue and red LEDs - Niizawa, Ignacio (2014)
Research on microalgae has grown significantly over the past few decades, due to their multiple uses and applications. The distribution of the density of radiant energy within the photo-bio-reactor and its impact on the growth of microalgae through the local rate of absorption of radiant energy is essential for the analysis, modeling and design of a photo-bio-reactor because of the light stratification inside a microalgal culture. In this work we develop a physical model and a computer simulation algorithm, in order to accurately predict the rate of absorption of photons in microalgal cultures at each point of a photo-bio-reactor irradiated with a light source made of different arrangements of LEDs emitting in blue and red spectral regions. Results showed that the average absorption rates in the culture irradiated with blue LEDs were higher than that irradiated with red LEDs. However, the radiation emitted by red LEDs rendered greater energy efficiency for biomass production compared to that emitted by blue LEDs. This facts are analyzed through the photon capture mechanism of microalgal antenna complex and photosystem interaction.